PASANG SURUT HUBUNGAN ISLAM-BARAT - Hamdani, Salman (Fakultas Dakwah IAIN Purwokerto, 2014)
This paper is a literature review (literature research) that uses John Esposito’s books as primary data sources and other figures’ statements about the relationship between Islam and the West as its secondary data source. The method of analyzing data used descriptive, interpretative, and analytical methods. The findings of this research are: first, based on historical fact, there is strong theological bond between Islam and the West, i.e. there are common ground and similarities between Islam and the West who inherited the Jewish and Christian traditions. These three religions inherited the tradition of Prophet Ibrahim. However, existing theological equation between Christianity and Islam became the cause of the collision between the two. Second, the historical problems between Islam and the West can be seen from the root of the conflicts, which include theological and political ones. Conflict between Islam and the West are covered with political motives. In contrast, religion is only used as a theological justification to culturally and theologically distinguish Islam and the West. Basically the difference is more driven by political interests. Third, as an effort to build a global coalition agreement, both sides should actively promote cooperation. Therefore, the most important thing is that the meet between Islam and the West should be interpreted as a civilization dialogue, not confrontation or distrust. the Building ideal relationship as well as the need for harmonization between Islam and Western civilization are also needed.